2021
DOI: 10.1371/journal.pone.0247746
|View full text |Cite
|
Sign up to set email alerts
|

The interplay of sleep duration, working hours, and obesity in Korean male workers: The 2010–2015 Korea National Health and Nutrition Examination Survey

Abstract: The purpose of this study was to clarify the odds ratio for association between working hours and obesity in Korean male wage workers and investigate the role of sleep duration. This study is a cross-sectional one using large-scale national data from the Korea National Health and Nutrition Examination Survey collected between 2010 and 2015 to evaluate 2,592 male wage workers (between the ages of 19 and 60 years). Obesity was defined as 25kg/m2 or more and working hours per week were categorized into <40, 40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…29 A large portion of the literature has reported that long working hours are linked with lower quantity and quality of sleep. 11,12,[30][31][32] Hence, it is believed that insufficient recovery due to sleep deprivation is considered a critical component of the pathway from long working hours to health problems. 12,33 Another experimental study revealed that long working hours reduced sleep time and increased fatigue.…”
Section: T a B L Ementioning
confidence: 99%
See 1 more Smart Citation
“…29 A large portion of the literature has reported that long working hours are linked with lower quantity and quality of sleep. 11,12,[30][31][32] Hence, it is believed that insufficient recovery due to sleep deprivation is considered a critical component of the pathway from long working hours to health problems. 12,33 Another experimental study revealed that long working hours reduced sleep time and increased fatigue.…”
Section: T a B L Ementioning
confidence: 99%
“…35 Second, workers with long working hours have less time to engage in healthy lifestyle habits, such as physical exercise and sufficient sleep. 30 Time constraints may leave some workers with few choices but to rely only on alcohol and smoking as coping strategies to relieve stress. Researchers have reported that a reduction in working time promotes regular exercise, decreases the likelihood of smoking, 36 and leads to beneficial effects on sleep quality and duration.…”
Section: T a B L Ementioning
confidence: 99%
“…Furthermore, insufficient sleep was found to have a mediating effect on the connection between working hours and obesity. Consequently, these findings suggest the importance of identifying factors such as working and sleeping hours for the prevention and management of obesity in wage workers [22].…”
Section: Autocorrelation and Correlationmentioning
confidence: 95%
“…In fact, Korea had the second highest number of working hours among OECD countries in 2022. The effects of these long working hours are considered an important factor in negative health outcomes, such as musculoskeletal symptoms, poor mental health, and decreased kidney function [17][18][19][20][21].…”
Section: Plos Onementioning
confidence: 99%